GEOCHEMICAL INVESTIGATION OF AQUIFER POLLUTION FROM WASTE MANAGEMENT. THE CASE OF KOMOTINI LANDFILL (GREECE) - Raco, B.; Dotsika, E.; Psomiadis, D.; Doveri, M.; Lelli, M.; Zisi, N.; Papakonstantinou, K.; Lazaridis, A. (Bulletin of the Geological Society of Greece, 2010)
According to European legislation, environmental control and monitoring of landfills has become of crucial importance. This study includes a thorough geochemical approach aiming to evaluate the environmental impact of the landfill of Komotini, N. Greece. Samples of waters were taken from inside the working landfill as well as from the area of the neighbouring old landfill. The waters were analyzed chemically (major elements and heavy metals) and isotopically (D and 18O). Also, biogas flow was measured and the ratio CH4/CO2. Based on the geomorphological, hydrogeological and land use data of the area, we proceeded to analyses of waters both from the area of the landfill and from the wider region (drainage basin). The obtained results were used to construct digital maps (GIS) in order to determine the special dispersion of the polluted aquifers. The biogas flow in the old and new garbage burial sites was measured by accumulation chamber device for methane and carbon dioxide ratio determination. The obtained results show an important agent of pollution in the water samples downstream from the landfill and in a distance more than 2km, along the dispersion of the leachate. The land use of the area was taken into account to evaluate the importance and the criticality of the situation.